ASI EKSKLUSIF DAN TINGGI BADAN IBU DENGAN KEJADIAN STUNTING PADA ANAK USIA 6 - 36 BULAN - Arnisam Arnisam; Nunung Sri Mulyani; Eva Fitriyaningsih; Desi Muntazirah (Poltekkes Kemenkes Semarang, 2020)
Background :Stunting is called a cross-generation nutritional problem caused by multifactors including genetic factors (maternal height). Another factor causing stunting is lack of nutrition. ASI fulfills all of the baby's nutritional needs, so breastfeeding status also affects the incidence of stunting.Objective : to determine the relationship of exclusive breastfeeding and maternal height with the incidence of stunting in children aged 6-36 months in the UPTD of the Ulee Kareng Health Center in Banda Aceh.Methods : This research is descriptive analytical research with cross sectional design with a quantitative approach. It was held on May-June 2019. The population of this study was all children aged 6-36 months in the UPTD of the Health Center Ulee Kareng Banda Aceh. The sample size was 81 children aged 6-36 months. The sampling technique in this study was accidental sampling. The instrument used was a questionnaire to determine toddler identity and the identity of the respondent. Measurement of height using microtoice, and body length was measured using an infrantometer Analysis of data using the chi square test with a 0.05 degree of confidence.Result : Based on the results of the study, children who received exclusive breastfeeding were 51.9%. Short mother 58%. Normal child 51.9%. There is a relationship between exclusive breastfeeding and maternal height with the incidence of stunting in children aged 6-36 months. With p-value 0.05. Namely exclusive breastfeeding with the incidence of stunting in children (p-value = 0.011). Maternal height with incidence of stunting in children (p-value = 0.028).Conclusion : Exclusive breastfeeding and maternal height have a relationship with the incidence of stunting in children aged 6-36 months in the UPTD of the Health Center Ulee Kareng Banda Aceh. So it is expected that mothers give exclusive breastfeeding for babies as an effort to prevent stunting.